Design and synthesis of fluorescent opioids for bioimaging - Lam, Raymond (2018)
Opioids are a class of alkaloid that have been used since pre-history for the treatment and control of pain. Morphine and codeine, the active ingredients in the opium latex from the plant Papaver somniferum, have been known since the 19th century. Although their use in the clinic is widespread, they suffer from various adverse effects, including euphoria, constipation, respiratory depression, tolerance, dependence. These last two side effects are of note, as they are responsible for increasing opioid addiction and related deaths in the United States, as well as in other parts of the world.